Peran Moderasi Kesulitan Keuangan pada Hubungan Penggantian Auditor dengan Determinannya - Elok Heniwati (Universitas Prasetiya Mulya, 2022)
Auditor switching has become an exciting topic when the auditing environment dynamics continues to develop. This study is intended to examine the relationship between auditor switching and their influential factors by considering the company's financial problems. Using logistic regression statistical methods to examine the data, this study shows that audit fees, KAP reputation, and company growth affect auditor switching, while audit opinion has no effect. Furthermore, financial distress can only influence the relationship between company growth and auditor switching. This study provides in-depth insight into the relationship between client firm characteristics and auditor changes mediated by financial distress. This study would expand on similar studies conducted in Indonesia. Given that the audit environment is constantly evolving, it is expected that the results of this study will enrich the existing literature.